On the (In)effectiveness of Fiscal Devaluations in a Monetary Union - Leopold von Thadden; Anna Lipinska (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper explores the fiscal devaluation hypothesis in a model of a monetary union characterised by national fiscal and supranational monetary policy. We show that a unilateral tax shift towards indirect taxes in one of the countries produces small but non-negligible long-run effects on output and consumption within and between the two countries only when international financial markets are perfectly integrated. In contrast to the existing literature, we find that short-run effects are not always amplified by nominal wage rigidities. We document also how short-run effects of the tax shift depend on the choice of the inflation index stabilised by the central bank and on whether the tax shift is anticipated.
Keywords: E61; E63; F42; 330